If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 3(2y + 5) = 1 Reorder the terms: y + 3(5 + 2y) = 1 y + (5 * 3 + 2y * 3) = 1 y + (15 + 6y) = 1 Reorder the terms: 15 + y + 6y = 1 Combine like terms: y + 6y = 7y 15 + 7y = 1 Solving 15 + 7y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 7y = 1 + -15 Combine like terms: 15 + -15 = 0 0 + 7y = 1 + -15 7y = 1 + -15 Combine like terms: 1 + -15 = -14 7y = -14 Divide each side by '7'. y = -2 Simplifying y = -2
| 13-0.5x=0.7x-23 | | 2+w/6=20 | | 155x=(136)(155)+136x | | 145x=(136)(145)+136x | | (8-b^2-4)-(1-8b^2)= | | 3+5(x-2)=20 | | 3(-4x+1)=3 | | 3(X-1)-(x-3)=0 | | 2x-4=3x+29 | | 210+70m=760-40m | | 62.52=27.39+t | | 8x+6.3=86.3 | | 66n+16=14 | | 3+t=-4 | | -17=5(2x+3)-12 | | 2x+1=7x-1 | | 27=-3u | | (16x+40)+5=8(x+8) | | 2t-3=-19 | | y=-4-19 | | 4w+6=22w | | W+19=47 | | 2a=2.8 | | 4m-2n=18 | | 7+3k=-14 | | 145x=(106)(145)+106x | | y=-4(-5)-19 | | 155x=(106)(155)+106x | | -3(n-2)+5n=2(-3n+4)-2n+1 | | 7x-3+5x+3=180 | | 4(3x-5)+6=2x-14 | | 24=-4m |